RANCANG BANGUN SISTEM ABSENSI PEGAWAI MENGUNAKAN QR CODE PADA KANTOR DESA SIDAMUKTI - Ahmad Fatoni; Rustam Effendi; Fikri Hadiyansyah; masum masum (Teknik Informatika Fakultas Ilmu Komputer, 2022)
ABSTRACT Employee attendance is an important factor for an agency or company to achieve goals, this is related to discipline and has an impact on the performance of each employee. Therefore, it is necessary to have special data collection to record attendance and absences so that work activities can be recorded in real time and well. There are many ways that can be done to achieve a good attendance information system, one of which is using computer technology where it is applied with a website-based attendance application. At the Sidamukti Village Office, Baros District, Serang Regency, Banten Province, the system used in the attendance process is still manual using a daily attendance book which has an impact on the efficiency and effectiveness of data collection, data search as well as data recap calculations that take a relatively long time. In addition, the risk of errors and loss of attendance data is even greater. Berdasarkan permasalahan diatas dibuatlah Rancang Bangun Sistem Absensi Pegawai Mengunakan QR Code Pada Kantor Desa Sidamukti Metode penelitian merupakan metode yang digunakan dalam pengumpulan data yang meliputi: metode riset, wawancara dan pustaka. Sedangkan pengembangan perangkat lunak menggunakan waterfall yang meliputi : analisa kebutuhan, desain, pengkodean, pengujian dan implementasi. Dengan dihasilkannya aplikasi absensi kepegawaian berbasis web dapat memberikan kemudahan dalam proses absensi, pencarian data dan perhitungan rekap absensi, serta meminimalisir kehilangan dan kesalahan pencatatan data absensi. Keywords: Employee Attendance, Attendance System, Website.